Beyond redundancy and multiplicity. Integrating phytolith analysis and micromorphology to the study of Brussels Dark Earth. (April 2016) - Vrydaghs, Luc; Ball, Terry B.; Devos, Yannick
Abstract: Multiplicity, when different phytolith morphotypes are produced within a taxon, and redundancy, when the same phytolith morphotypes are produced by different taxa, are persistent challenges in phytolith analysis. This article discusses and demonstrates how micromorphological and phytolith analyses of soil thin sections can be integrated to address issues of redundancy and multiplicity, as well as depositional history when studying archaeological soils and sediments. Opal phytoliths are created by the accumulation and precipitation of monosilicic acid (Si(OH)4 ) within plant tissues. Usually the process produces a variety of phytolith morphotypes with specific anatomical distribution within the plant tissues. When deposited in soil, phytoliths from decomposed plant tissue become microfossils of the plants in which they were produced. Decomposition or decay of plant tissue can take place either before or after it is incorporated into the soil matrix. When decay takes place after plant tissue is incorporated into a soil matrix, the anatomical distribution of the phytoliths within the tissue is often preserved, if the soil has not been affected by post-burial disturbances. Typically, analysis of phytoliths in soil begins with removing the phytoliths from the soil using techniques such as heavy liquid floatation, thereby destroying much of the distribution pattern of the phytoliths within the matrix and losing potentially important data. Analysing phytoliths within soil thin sections is becoming a more frequently applied alternative to analysing phytoliths extracted from the soil. Thin sections preserve the distribution patterns of phytoliths within an archaeological deposit or soil and as such can help researchers answer questions concerning redundancy, multiplicity and depositional history. In this study we demonstrate how the integration of phytolith analysis with micromorphological analysis of a series of thin sections made from Brussels urban archaeological deposits that have complex and multiphase formation histories can be used to differentiate phytoliths with different histories. The potential for improved botanical identification of the different groups of phytoliths is also discussed. Highlights: Redundancy and multiplicity compose a complex backdraw to botanical identification of phytoliths. These issues are amplified by standard phytolith procedures mixing phytoliths. The analysis of thin sections provides an alternative to these issues. Phytolith analysis of thin sections provides opportunities for botanical identification by morphometric analysis in archaeological contexts.